Arrhythmias Following Patent Foramen Ovale Closure: An Unsolved Enigma - Aikaterini-Eleftheria Karanikola; Stergios Soulaidopoulos; Ioannis Leontsinis; Eirini Dri; Marios Sagris; Athanasios Kordalis; Konstantinos Aznaouridis; Dimitrios Tsiachris; Konstantinos Tsioufis (Life)
Patent foramen ovale (PFO) closure has proven to be an effective method of reducing the risk of recurrent stroke in patients with embolic stroke of unknown origin (ESUS). One of the most recognized post-procedural complications is the de novo occurrence of supraventricular arrhythmias, mainly atrial fibrillation, in the first three months following PFO closure. Earlier studies reported the incidence to be around 3.4–7%; however, this percentage has risen in recent studies up to 21%. The pathogenesis behind this type of arrhythmia is complex and not clearly understood, although it seems that direct effects of the device on the atria, as well as an inflammatory response, are the two most prevalent mechanisms. Management of this complication might be challenging given the heterogenicity of patient characteristics, so an individualized approach is most wisely followed. This review aims to present the current data on the incidence, pathogenesis and therapeutic strategies behind this rather common concern in an era of increasing transcatheter interventions for PFO.